2021
DOI: 10.3390/molecules26113339
|View full text |Cite
|
Sign up to set email alerts
|

Antiprotozoal and Antibacterial Activity of Ravenelin, a Xanthone Isolated from the Endophytic Fungus Exserohilum rostratum

Abstract: The natural compound ravenelin was isolated from the biomass extracts of Exserohilum rostratum fungus, and its antimicrobial, antiplasmodial, and trypanocidal activities were evaluated. Ravenelin was isolated by column chromatography and HPLC and identified by NMR and MS. The susceptibility of Gram-positive and Gram-negative bacteria strains to ravenelin was determined by microbroth dilution assay. Cytotoxicity was evaluated in hepatocarcinoma cells (HepG2) and BALB/c peritoneal macrophages by using MTT. SYBR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Aspergillus sp. YXf3, an endophyte residing inside the leaves of Ginkgo biloba, yielded some novel p-terphenyls named prenylterphenyllin D (187), prenylterphenyllin E (188), and 2 -O-methylprenylterphenyllin (189), along with the known compounds prenylterphenyllin (190) and prenylterphenyllin B (191,Figure 11). Compounds 187-191 displayed antibacterial activity against X. oryzae pv.…”
Section: Aspergillusmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspergillus sp. YXf3, an endophyte residing inside the leaves of Ginkgo biloba, yielded some novel p-terphenyls named prenylterphenyllin D (187), prenylterphenyllin E (188), and 2 -O-methylprenylterphenyllin (189), along with the known compounds prenylterphenyllin (190) and prenylterphenyllin B (191,Figure 11). Compounds 187-191 displayed antibacterial activity against X. oryzae pv.…”
Section: Aspergillusmentioning
confidence: 99%
“…Ravenelin (440, Figure 24) was extracted from Exserohilum rostratum, an endophyte of Phanera splendens, an endemic medicinal plant of the Amazon region. Ravenelin (440) displayed antibacterial activity against B. subtilis and S. aureus with MIC values of 7.5 and 484 µM, respectively (amoxicillin MIC against B. subtilis and S. aureus 1.3 and 21.4 µM; another positive control terramycin MIC against B. subtilis and S. aureus 16.3 and 16.3 µM, respectively) [190].…”
Section: Minor Taxa Of Anamorphic Ascomycetesmentioning
confidence: 99%
“…Some studies have shown that compounds isolated from endophytic fungi have antimicrobial activity against the phytopathogenic bacteria of the Xanthomonas genus [28,29]. Thus, the ACN extract was fractionated in CC, giving fractions FACN1 to FACN6; these fractions were analyzed by 1 H NMR, and fractions FACN4 and FACN5 showed spectrums with patterns of xanthones, which is a class of compound that has reported diverse biological activities [30][31][32]. Isolation by CC procedure led to the compounds S1 and S2.…”
Section: Discussionmentioning
confidence: 99%
“…From the Brazilian biodiversity, the fungus Exserohilum rostratum ( Figure 6 ) was isolated from Bauhinia guianensis [ 209 ] and Phanera splendens [ 210 ], which are typical Amazonian plants used in popular medicine to combat infections. Among the SMs produced by this species are the polyketide monocerin, ergosterol peroxide, annularins, and ravenelin, which presented moderated antimicrobial activity on B. subtilis , S. aureus , E. coli , P. aeruginosa , and B. subtilis and Salmonella typhimurium [ 209 , 210 ].…”
Section: Studies Of Fungal Secondary Metabolites As Cytotoxic and Ant...mentioning
confidence: 99%